Characterisation of Plant Growth-Promoting Endophytic Bacteria from Sugarcane and Their Antagonistic Activity against Fusarium moniliforme - Nittaya Pitiwittayakul,; Duanpen Wongsorn,; Somboon Tanasupawat, (Tropical Life Sciences Research, 2021)
The use of endophytic bacteria in agriculture provides an effective way of improving crop yield and significantly reducing chemical usage, such as fungicides. This research was conducted to explore endophytic bacteria with plant growth promotion (PGP) and antifungal activities against Fusarium moniliforme AIT01. In this study, we obtained 52 isolates of endophytic bacteria associated with the roots and stems of sugarcane from Nakhon Ratchasima province, Thailand. In vitro antagonistic activity test showed that 14 out of 52 isolates had antagonistic activity against the fungal pathogen F. moniliforme AIT01. These antagonistic endophytic bacteria were identified as belonging to six different species as follows: Nguyenibacter vanlangensis, Acidomonas methanolica, Asaia bogorensis, Tanticharoenia aidae, Burkholderia gladioli and Bacillus altitudinis based on phenotypic characteristics, along with phylogenetic analysis of their 16S rRNA gene sequences. Seven isolates effectively inhibited F. moniliforme AIT01 mycelial growth by up to 40%. The volatile compounds of six isolates reduced the growth of F. moniliforme AIT01 by over 23%. Moreover, riceberry rice seedlings previously treated with B. gladioli CP28 were found to strongly reduce infection with phytopathogen by 80% in comparison to the non-treated control. Furthermore, the isolates also showed relevant PGP features, including ammonia production, zinc and phosphate solubilisation, auxin and siderophore biosynthesis. These results demonstrated that the tested endophytic bacteria could be successfully utilised as a source of PGP and biocontrol agent to manage diseases caused by F. moniliforme.